Structural and optical studies of cadmium sulfide quantum dots-graphene oxide-chitosan nanocomposite thin film as novel SPR spectroscopy active layer - Saleviter, Silvan; Yap, Wing Fen; Sheh Omar, Nur Alia; Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Abdullah, Jaafar; Mat Zaid, Mohd Hazani (http://www.hindawi.com/, 2018)
The aim of this study is to prepare and study the cadmium sulfide quantum dot-graphene oxide-chitosan composite thin film. This composite material was coated on top of the gold layer by a spin-coating technique as a modification of the active layer for metal ion sensing using surface plasmon resonance spectroscopy (SPR). The composite material was prepared using a simple wet solution mixing method. An atomic force microscope (AFM) shows that the addition of GO increased the roughness of the composite thin film and the presence of CdS QDs cannot be observed as the size of the QDs are very small. The morphology of the nanocomposite material was observed using transmission electron microscopy (TEM). From the TEM images, it is observed that the materials mixed to form a nanocomposite material. The optical properties of the thin film via UV-Vis spectroscopy shows that the absorbance peaks of the thin film can be observed around 220 nm to near 300 nm, and the band gaps are around 4.0 eV. Lastly, the prepared thin film was tested as an active layer for metal ion detection via surface plasmon resonance (SPR), where the angle shift was observed to show that the prepared thin film has high potential for Co2+ ion detection.